One-dimensional nonlinear consolidation of a hyperbolic model with continuous drainage boundary under cyclic dynamic loading - Huang, Zhigang; Wang, Xuan; Tong, Lihong; Wang, Jue; Zhong, Peijia; Xu, Zhihua (Frontiers in Earth Science, 2025)
IntroductionSoft clay foundations exhibit complex nonlinear consolidation characteristics under cyclic loading, which significantly affects long-term stability.MethodsThis study proposes an innovative one-dimensional nonlinear consolidation analysis framework by comprehensively considering continuous drainage boundary conditions and cyclic dynamic loads, more realistically simulating the behavior of soft clay under complex loads and actual drainage boundary conditions in engineering practice. Additionally, under the assumptions of proportional reduction in permeability and compression coefficients and uniform initial effective stress distribution, the analytical solutions for effective stress and settlement during the consolidation process under cyclic loading are derived through variable substitution and separation methods.ResultsThe consistency of the solution with that of Terzaghi’s permeable boundary case verifies the correctness and convergence of the proposed solution. Moreover, it is found that in the hyperbolic consolidation model, the variation of the initial void ratio has a negligible effect on the consolidation and settlement characteristics of the soil.DiscussionAn increase in the initial compression modulus and the slope n of the compression curve will reduce the fluctuation amplitude of the soil consolidation settlement curve and slow down the development of soil consolidation settlement. This study enhances the predictive capability for evaluating the behavior of soft clay foundations under complex loading and drainage conditions.